Negative pressure drainage relieves respiratory discomfort for patients with medical face masks under ocular surgeries during COVID-19 - De-Hua Li (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM:To report our precaution practices for ocular surgeries under local anesthesia during COVID-19 outbreak and evaluate the respiration situation among the patients with medical face masks under ocular surgeries.METHODS:Sixty Chinese patients needed eye surgery treatment were recruited and given medical face masks as one of the COVID-19 precaution practices during eye surgery with local anesthesia. Oxygen supplementation and negative pressure drainage were applied to relieve the potential respiratory discomfort, and the respiratory comfort score was evaluated.RESULTS:Patients with medical face masks experienced mild to moderate respiratory discomfort with an overall mean score of 2.34±0.73. Supplementation of oxygen together with negative pressure drainage relieved this discomfort(overall mean score of 0.15±0.75; P<0.001). There is no gender and operation time difference on respiratory discomfort or discomfort relieve. Failure in negative pressure drainage led to severe respiratory discomfort.CONCLUSION:Negative pressure drainage could maintain the respiratory circulation in patients with medical face mask under eye surgery with local anesthesia. Application of medical face masks in patients under surgeries is recommended to protect the medical practitioners during the operations within COVID-19 outbreak.